PEMBERLAKUAN SYARI'AT ISLAM DI BANTEN - B. Syafuri (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Syari'a is religious value expressed functionally and concretely as a way that guides human 's life for virtue both in the World and in the hereafter. Islamic law (syari'a) is naturally put into effect in order to be Islamic law as a sub-system of National (positive) law. Based on the history of Banten, the sultanate of Banten had ever implemented the Islamic law as the law applied in the sultanate. It was based on the evidence that in the period of Sultan Ageng Tirtayasa, the amputation law for the ruslers had ever been applied. The historical religiosity and its actualization in Banten nowadats are potential to implement Islamic law comprehensively. Moreover, Bantenese society remains holding tightly on the Islamic values that have become the culture and principle in regulating their life as proven in the legislative of Banten that has issued local regulations of Islamic laws in the districts and cities of Banten. Optimalization of Islamic law implementation in Banten still goes on up to now through a significant numbers of the religious culture in the society, Islamic education institutions, religious proselytizing (dakwah), muamalah and al-akhwal syakhsiyyah. The challenge in endeavoring the implementation of Islamic law generally lies on the lack of the society's understanding on the detail and the meaning of Islamic law. The human sources of Banten (the strategic elites) support the implementation of Islamic law as both culture and values that can be absorbed in various law and regulations. Keywords: Syari'at Islam, Banten, perda syari'ah.